1960
DOI: 10.1136/gut.1.2.111
|View full text |Cite
|
Sign up to set email alerts
|

A Test of Pancreatic Function in Man Based on the Analysis of Duodenal Contents after Administration of Secretin and Pancreozymin

Abstract: Pancreozymin in man as in animals appears to act as a specific enzyme stimulant. The preparations of pancreozymin used in these experiments also contain cholecystokinin, which causes the gall bladder to contract, and a smooth muscle stimulant, possibly substance P.The (Lagerlof, 1939(Lagerlof, , 1942 Diamond, Siegel, Gall, and Karlen, 1939;Diamond andSiegel, 1940, 1941;Comfort and Osterberg, 1940;Pratt, Brugsch, and Rostler, 1940;Pollard, Miller, and Brewer, 1942;Lake, 1947;Dornberger, Comfort, Wollaeger, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

1965
1965
1981
1981

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(63 citation statements)
references
References 28 publications
3
60
0
Order By: Relevance
“…'Parallel' secretion of pancreatic enzymes was also reported in response to injections of secretin (Burton, Evans, Harper, Howat, Oleesky, Scott, and Varley, 1960) and of pancreozymin (Burton et al, 1960;Creutzfeldt, 1964;Rick, 1965;Sarles, Figarella, Prezelin, and Souville, 1966;Ammann, Tagwercher, Kashiwagi, and Rosenmund, 1968). On the other hand, Guth, Komarov, Shay, and Style (1956) found statistically significant day-to-day deviations from 'parallelism' in the enzyme response to food in dogs, while Worning and Mullertz (1966) (Burton et al, 1960) Gibbs (1950) showed that the secretion of amylase was sometimes grossly defective in normal infants, whose secretion of trypsin was normal, while Choi, Goldstein, Wirts, and Menduke (1967) recommended the measurement of trypsin because trypsin secretion could be abnormal when amylase secretion remained normal in patients with pancreatic disease. In a much earlier study, Diamond, Siegel, Gall, and Karlen (1939) had already suggested that the practice of estimating only one enzyme was not an adequate measure of total pancreatic capacity to secrete enzymes, because they found frequent dissociation between trypsin and amylase secretion.…”
Section: Discussionmentioning
confidence: 79%
“…'Parallel' secretion of pancreatic enzymes was also reported in response to injections of secretin (Burton, Evans, Harper, Howat, Oleesky, Scott, and Varley, 1960) and of pancreozymin (Burton et al, 1960;Creutzfeldt, 1964;Rick, 1965;Sarles, Figarella, Prezelin, and Souville, 1966;Ammann, Tagwercher, Kashiwagi, and Rosenmund, 1968). On the other hand, Guth, Komarov, Shay, and Style (1956) found statistically significant day-to-day deviations from 'parallelism' in the enzyme response to food in dogs, while Worning and Mullertz (1966) (Burton et al, 1960) Gibbs (1950) showed that the secretion of amylase was sometimes grossly defective in normal infants, whose secretion of trypsin was normal, while Choi, Goldstein, Wirts, and Menduke (1967) recommended the measurement of trypsin because trypsin secretion could be abnormal when amylase secretion remained normal in patients with pancreatic disease. In a much earlier study, Diamond, Siegel, Gall, and Karlen (1939) had already suggested that the practice of estimating only one enzyme was not an adequate measure of total pancreatic capacity to secrete enzymes, because they found frequent dissociation between trypsin and amylase secretion.…”
Section: Discussionmentioning
confidence: 79%
“…In series reported by the above-quoted authors, the coefficient of variation ranged from 22 to 43%. Several authors, therefore, tried to decrease the variation of enzyme output by stimulating the enzyme secretion with CCK-PZ before or after secretin injection (Marks and Tompsett 1958;Burton et al 1960;Sun and Shay 1960;Dreiling and Janowitz 1962). But, the coefficient of variation in enzyme was not decreased by adding CCK-PZ injection to the secretin test on the whole.…”
Section: Discussionmentioning
confidence: 99%
“…The volume of juice is abnormally high but the bicarbonate output is usually normal. The response is seen in gall bladder disease, after cholecystectomy and, especially, in cirrhosis and haemochromatosis, (Banwell et al, 1967a;Bode et al, 1972;Burton et al, 1960a;Wormsley, 1970b;Zieve and Mulford, 1967).…”
Section: Persistent Reduction Indicates Some Permanentmentioning
confidence: 99%
“…For chronic pancreatitis, pancreatic carcinoma, and "normals" the order of increasing diagnostic accuracy was: scanning, bicarbonate concentration, trypsin output, 8SSe output, 8SSe concentration, hypotonic duodenography, duodenal juice volume. In cases of surgical jaundice, however, the intubation method (Burton et al, 1960a) gives greater accuracy than hypotonic duodenography (Bourke et al, 1972). The addition of cytological examinations to the range of investigations improves the detection rate in cases of carcinoma of the pancreas, bile ducts or ampulla (Bourke et al, 1972;Nundy et al, 1974).…”
Section: Comparison Of Pancreatic Function Tests and Selection Of Tesmentioning
confidence: 99%